Koranic Schools in Niger : How Much Can Be Learned from Existing Data? - Male, Chata; Nayihouba, Ada; Wodon, Quentin (Taylor and Francis, 2022)
The term Koranic school is often used to describe schools that are not part of the formal education system and typically place a strong emphasis on memorizing the Koran in Arabic, as well as on knowledge of Islamic religious education and practice. Using data from Niger as a case study, this paper provides data on trends in the share of individuals that have a Koranic education, a formal education, or no education at all, as well as a basic profile (univariate and multivariate) of children with Koranic education, formal education, or no education at all. In addition, the potential impacts of Koranic education in comparison to formal education or no education at all on outcomes such as literacy and numeracy, labor market earnings, household consumption, assets and perceptions of well-being, and infant mortality is analyzed.